THE RELATIONSHIP OF KNOWLEDGE ABOUT SEXUALLY TRANSMITTED INFECTIONS WITH THE SEXUAL BEHAVIOR OF ADOLESCENT WOMEN IN SMKN 5 JEMBER - Maulidia Fahmadina Rozana; Ratna Dwi Jayanti; Gatut Hardianto (UNIVERSITAS AIRLANGGA, 2023)
Introduction: Adolescence is a period in which hormonal developments affect physical, psychological and cognitive development. At this time adolescents show an interest in sexuality so that adolescents are at risk of contracting Sexually Transmitted Infections (STIs). Many factors can influence adolescent sexual behavior, one of which is knowledge about STIs. Adolescents must have good knowledge to control their sexual behavior in order to avoid sexual behavior that is at risk of STIs. This study aims to analyze the relationship between adolescent knowledge of STIs and female adolescent sexual behavior. Method: This research is an observational analytic study with aresearch design cross sectional. The number of samples as many as 103 teenagers who fit the inclusion criteria. The sampling technique was carried out by total sampling. the independent variable is adolescent knowledge about STIs, while the dependent variable is adolescent sexual behavior. The collected data was tested with thestatistical Fisher Exact Testtest. Results: The results showed that as many as 68 respondents (66.0%) had less knowledge and 35 respondents (34.0%) had good knowledge. The variable of adolescent sexual behavior was found that 90 people (87.4%) had sexual behavior that were not at risk of STIs and 13 people (12.6%) had STI risky sexual behavior. After thecarried out Fisher Exact Test was , the p value = 0.357 (p>0.05) which means that statistically there is no relationship between knowledge about STIs and sexual behavior of adolescent girls. Conclusion: There is no relationship between knowledge of STIs and sexual behavior of adolescent girls at SMKN 5 Jember